Identification and characterization of cyclophilin A-binding protein genes of African Trypanosomes. - Ondondo, B.O. (Kenyatta University, 1999)
African trypanosomosis is characterized by the profound suppression of the hosts' immune system and Cylophilin (Cyp) proteins have been implicated. Previous research findings have attributed the immunosuppression observed to a Trypanosome Immunosuppressive Fraction (TISF) which shows suppressive, chemotactic and chemokinetic activities. The TISF was recovered by a single HPLC-Superose chromatography based on molecular weights and was shown to contain proteins ranging from 18-70 kDa while a SDS-PAGE analysis of this fraction showed proteins of 20,50 and 70 kDa. These findings strongly suggest interactions between some proteins in this fraction. Cyp A, a 20-kDa protein was found as a major component of the TISF from T. brucei and T. congolense and was shown to have chemotactic activity on macrophages, the key host cell type implicated in immunosuppression. Since Cyp is present as a major component of TISF and yet it is only 20 kDa, then this is highly suggestive that there is interaction of Cyp with other proteins in the TISF hence the 18-70-kDa range in the molecular weight. The fact that Cyp is present as a major component of TISF yet it does not show suppressive activities reveals that the suppressive activities of the TISF may be due to other proteins present in this fraction. It was therefore hypothesized that Cyp-Binding proteins may contribute to the immunosuppression observed during trypanosomosis. Targeted immune responses against Cyp A-BPs may allow improved control of trypanosomosis, thus research efforts were focused on the identification and characterization of Cyp A-BPs for vaccine development. In this study four genes encoding African T. brucei and T. congolense Cyp-BPs were identified, isolated and characterized by use of the yeast two-hybrid system. The Cyp gene was cloned into the shuttle vector pGBT9 to generate the pGBT9 + Cyp recombinant clone. T. brucei and T.Congolense genomic DNA libraries were generated and cloned into the shuttle vector pGAD424 to construct the pGAD424+Library recombinant. DNA was extracted from the PGBT9+Cyp and the pGAD424+library recombinant clones and used to transform competent yeast cells. Interaction between Cyp and any protein was tested by the -galactosidase assay, which showed blue colour for Cyp-BPs interactions and white for non-interacting proteins. Four genes encoding T. brucei and T. congolense Cyp-BPs were identified and isolated and were sequenced in both directions using -dATP (-33P) radiolabelled primers. A Genebank search revealed one of the clones to be in part similar to the Hsp83, while the other three no similarity with any gene in the Genebank. This may imply that the three clones carry new or unknown trypanosome genes, or the sequenced portions do not code for any significant proteins. Southern blot hybridization analyses of the four clones with T. congolense and T. brucei genomic DNA and all yielded positive results, which confirmed that the clones carry trypanosome genes and not baceterial or yeast genes. Efforts to identify a T. congolense homologue for one of the T. brucei Cyp-BPs by plaque hybridization of T. congolense cDNA and genomic DNA libraries and also by hybridizing the T. brucei Cyp-BP probe with a T. congolense genomic DNA Southern blot did not show positive results. This may imply low levels of expression of the gene in T. congolense and/or too low homology between the two homologues. It could also be due to high immunological pressure from the host or could be the T. congolense homologue of this gene does not occur at all. Northern blot hybridization of T. brucei and T. congolense RNA to establish the sizes and expression levels of the corresponding mRNA and also to establish whether or not the genes are developmentally regulated were negative including the control set up using radiolabelled Cyp as probe. This may be as a result of experimental inadequacies such as fewer amounts of RNA, inefficient transfers, high stringency hybridization and washing conditions and may be RNA degration. It may also be due to low copy numbers of the Cyp-BP genes hence resulting in very few mRNA transcripts. However fragments of PCR products obtained from the amplification of total T.b brucei ss-cDNA using mini-exon primers, oligodT primers and a forward and reverse primers internal to one of the T. brucei Cyp-BP clones were shown to hybridize with the radiolabeled clone. Since mini-exon sequences are specific to mRNA this result confirm that the clone can be transcribed to RNA and can therefore be translated to proteins.